2021
DOI: 10.1002/npr2.12207
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Secondary Traumatic Stress Scale‐Japanese version

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition, Chinese traditional culture places a high value on collectivism and interpersonal communication, leading to individuals experiencing job stress primarily through interpersonal relationship [ 46 ]. This is particularly true for individuals who identify with collectivist cultures, as they typically strive to avoid explicit interpersonal conflict in their interactions [ 47 ]. Moreover, the Cronbach’s α coefficient of the revised HCJSQ is 0.903, and the Spearman-Brown coefficient of the revised aggregate table is 0.904, which indicates that the reliability of the revised scale is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chinese traditional culture places a high value on collectivism and interpersonal communication, leading to individuals experiencing job stress primarily through interpersonal relationship [ 46 ]. This is particularly true for individuals who identify with collectivist cultures, as they typically strive to avoid explicit interpersonal conflict in their interactions [ 47 ]. Moreover, the Cronbach’s α coefficient of the revised HCJSQ is 0.903, and the Spearman-Brown coefficient of the revised aggregate table is 0.904, which indicates that the reliability of the revised scale is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…; ztime difference. By careful analysis of the items contained in the two dimensions of C-STSS, it can be found that the first dimension-stress dimension (items 1,4,5,7,8,9,11,15,16,17) mainly describes the influence of STS on helpers' daily life and psychological state (including sleep, mood, concentration, enthusiasm, etc.). And dimension 2-invasion and avoidance dimension (items 2, 3, 6, 10, 12, 13, 14) mainly describe the content related to the trauma victims they help.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used by doctors, nurses, midwives, respiratory therapists, mental health workers and other social workers in many regions (9)(10)(11)(12). It has been translated into Hungarian (13), French (14), German (15), Japanese (16) and other languages.…”
Section: Introductionmentioning
confidence: 99%
“…The tool includes a total of 17 different questions that measure stress using five-point, self-rating scales with responses ranging from 1 to 5, with 1 = never and 5 = very often. The questions are clustered into the three elements of STS: (i) intrusion (questions 2, 3, 6, 10, and 13), (ii) arousal (questions 4, 8, 11, 15, and 16), and (iii) avoidance (questions 1, 5, 7, 9, 12, 14, and 17) [ 24 , 25 ]. In its assessment of stress levels, the questionnaire focuses on the respondents’ experiences in the last seven days.…”
Section: Materials and Designmentioning
confidence: 99%
“…The scores range between 17 and 85, with the higher scores indicating higher levels of STS. The STSS scores have the following interpretation: <28 indicating little or no STS, 28–37 indicating mild STS, 38–43 indicating moderate STS, 44–48 indicating high STS, and 49 and above indicating severe STS [ 24 , 26 ].…”
Section: Materials and Designmentioning
confidence: 99%